Karakteristik Agronomi Tanaman Kapas (Gossypium sp.) dan Pengaruhnya terhadap Produksi Kapas Menggunakan Analisis Lintas - Fauziah, Virda; Setoko, Ujang; Salim, Abdurrahman; Madjid, Abdul (Jurnal Agro Industri Perkebunan, 2023)
The cotton plant is a fiber plant that is commonly used as a raw material for textiles, beauty, and health products. To increase cotton production, the development of superior varieties using plant breeding methods in cross-analysis is necessary. The cross-analysis method is used to determine the agronomic traits that affect cotton production, by selecting yield through several other characteristics related to yield. The aim of this study was to identify which agronomic characters can be used as selection criteria to increase cotton production using cross-analysis. The research was conducted at Politeknik Negeri Jember, and included 12 independent variables and one response variable, namely cotton production. The method used in this study was to perform correlation analysis, cross-analysis, calculate direct and residual contributions, and select agronomic characters that can be used as selection criteria. The results showed that the number of fruit characters had the highest correlation with cotton production (RX9Y = 0.835). Cross-analysis was carried out, and the highest direct effect was found between the number of fruit characters and cotton production (PX9Y = 0.971). The highest direct contribution was found in the character of the number of fruit, which had a total contribution of 98.321% and residue of 1.679%. Therefore, the agronomic character that can be used as a direct selection criterion is the number of fruits.